2017
DOI: 10.1080/07399332.2017.1352588
|View full text |Cite
|
Sign up to set email alerts
|

Sexual life of women in the climacterium: A community-based study

Abstract: Our purpose of conducting this community-based study was to determine sexual functions of women in climacterium and effects of menopausal symptoms on sexual functions. It was descriptive, cross-sectional, and community-based. The study sample consisted of 282 climacteric women. Menopause Rating Scale (MRS), Female Sexual Function Index (FSFI), and Sexual Satisfaction Scale for Women (SSS-W) were used for data collection. The total score was 13.42 ± 8.82 for MRS, 18.73 ± 9.79 for FSFI, and 82.56 ± 18.07 for SSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…A similar rate was reported in a sample of 14,480 women in Israel aged 18 and older (28%) [17]. Studies have tended to report inflated rates in "normal" populations (19-50%), with rates increasing among those with sexual complaints (68-75%) and being as high as 79% among post-menopausal women in Turkey [18]. A study published in JAMA by Laumann and colleagues found that decreased female sexual desire over the life course was reported, in answer to a single question, by 43% of women [19].…”
Section: Introductionsupporting
confidence: 76%
“…A similar rate was reported in a sample of 14,480 women in Israel aged 18 and older (28%) [17]. Studies have tended to report inflated rates in "normal" populations (19-50%), with rates increasing among those with sexual complaints (68-75%) and being as high as 79% among post-menopausal women in Turkey [18]. A study published in JAMA by Laumann and colleagues found that decreased female sexual desire over the life course was reported, in answer to a single question, by 43% of women [19].…”
Section: Introductionsupporting
confidence: 76%
“…The FSFI mean score was determined as 23.8±8.0 in the present study. In the literature, the FSFI mean score has been reported to be between 18.7 and 25.2 2,8,12,15…”
Section: Discussionmentioning
confidence: 99%
“…17 A study conducted by Kokcu and Andaç among Turkish population concluded that the sexual function worsened by the increasing number of symptoms associated with menopause. 21,22 It is known that the sexual functions of women in menopause worsen with the atrophic changes in the urogenital system that form together with estrogen deficiency. 6 So sexual function disorders can be accepted as a symptom of menopause.…”
Section: Discussionmentioning
confidence: 99%